2021
DOI: 10.1101/2021.04.12.21255366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation to Modulate fMRI Drug Cue Reactivity in Methamphetamine Users: A Randomized Clinical Trial

Abstract: Transcranial direct current stimulation (tDCS) has been studied as an adjunctive therapeutic option to alter maladaptive cortical excitability, activity, and connectivity associated with chronic substance use via the application of a weak direct current through the brain. The underlying mechanism of action remains ambiguous, however. We present a randomized, triple-blind, sham-controlled, clinical trial with two parallel arms conducted to determine the neural substrates of tDCS effects on drug craving using an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…This systematic review aims to provide a comprehensive overview of the entire FDCR field and the broad inclusion criteria for study participants included studies of individuals who met SUD diagnostic criteria and those who used substances without meeting such criteria and did not exclude studies of participants with various comorbidities. These and the methodological heterogeneities reported in this systematic review prevent us from performing a meta-analysis across studies, but future meta-analyses and mega-analyses of clusters of studies in the database are possible and facilitated by our ongoing effort to catalog and share FDCR studies …”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review aims to provide a comprehensive overview of the entire FDCR field and the broad inclusion criteria for study participants included studies of individuals who met SUD diagnostic criteria and those who used substances without meeting such criteria and did not exclude studies of participants with various comorbidities. These and the methodological heterogeneities reported in this systematic review prevent us from performing a meta-analysis across studies, but future meta-analyses and mega-analyses of clusters of studies in the database are possible and facilitated by our ongoing effort to catalog and share FDCR studies …”
Section: Methods and Resultsmentioning
confidence: 99%
“…Detailed methods and results of the systematic review sections are presented in the eMethods and eResults in the Supplement, and the search terms and syntax can be found in eTables 1 and 2 in the Supplement. This study followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) reporting guideline, and the protocol for this systematic review was preregistered . The annual update of this live systematic review can be found online .…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Task design should activate brain regions related to the desired brain state one wishes to target. Fatigue or learning effects, including adaptation or habituation that can cause a significant decrease of the BOLD response, should be minimized during task performance [94][95][96][97].…”
Section: Task-based Fmri Designmentioning
confidence: 99%
“…This study was conducted in accordance with the Declaration of Helsinki and all methods were carried out following relevant guidelines and regulations. More details on inclusion and exclusion criteria can be found here [27].…”
Section: Participantsmentioning
confidence: 99%
“…T1 and T2-weighted MRI data were used to generate head models for each individual to simulate electric fields (Figure 3). More details on neuroimaging and tDCS parameters can be found here [27]. fMRI data preprocessing fMRI preprocessing was performed in AFNI.…”
Section: Data Collection Proceduresmentioning
confidence: 99%